Evaluasi Strategi Guru dalam Meningkatkan Mutu Belajar Siswa di SMP Negeri 1 Pancur Batu - Jannah, Dawi Nur; Lubis, Arif Abdul Gani (Lembaga Yasin AlSys, 2023)
This research was conducted by researchers while in the field as one of the teaching staff at State Junior High School 1 Pancur Batu which is one of the schools accredited A, as a National Adiwiyata school towards independent adiwiyata, as well as a healthy school, even though Pancur Batu 1 Public Middle School is a school located less strategic because it is located on the outskirts of Medan city, in a neighborhood where most of the population has a lower level of education and lower middle class households. There have been other researchers who have conducted research at this school with this battle. We all know that education has a big role in the progress of the nation. School is an institution where education is held in the hope of citizens for a brighter future life. Education is one of the efforts that can be made by school teachers to become an institution where people hope for better insights into life in the future. Therefore, efforts to improve the quality of education are a shared responsibility, especially the principal as the highest leader in the school. Schools need a school principal who is qualified and has extensive knowledge of school management to obtain good performance and performance. For this reason, it is necessary to reform and improve the quality of education through the management sector. In Indonesia, education is regulated by teachers in Law number 20 of 2003 concerning National Education System Based on the above understanding, education has a crucial systematic meaning that is realized and planned. With the intelligence possessed by students, they can develop their talents and interests to realize goals optimally through the existing learning process. The quality of educational outcomes is determined by polyfactors, especially education management. The achievement of quality as a result of education is influenced by many factors, especially educational management. Based on that there is a relevant and Christian influence between the leadership of school principals on school-based management in improving quality. Principal leadership plays a crucial role in managing education management to achieve school goals efficiently and effectively. The school principal as a leader must have the right strategy as a basis for making decisions to achieve goals. This is inseparable from improving the strategy in each organization or forum. the difference is whether the tactic fulfills all elements perfectly, is effective and efficient in its application. This is mainly due to its very basic nature in the holistic application of the organization's mission to create, maintain and share its existence in the medium term, including the long term. Supporting factors in improving the quality of education at Pancur Batu 1 public junior high school means that the educators whose teachers at the school have qualified S1 and S2 education who have received educator certification, loyal and qualified educational administration staff, clear work programs and assignments, facilities that support activities learn how to teach. While the inhibiting factors in raising the quality of education in public junior high school 1 Pancur Batu means the low learning motivation of students, as long as staffing resources are not optimal, the low level of teacher discipline. Efforts made to improve the quality of education include: intensifying guidance and counseling activities, forming an atmosphere interesting learning and give appreciation to students who succeed such as gifts and scholarships, involve the employees concerned in education and staff training. The background to the establishment of SMP Negeri 1 P.Batu was originally to educate the nation's children because it was under the auspices of the direct government with the aim of educating and creating the characteristics of students, but the school was growing rapidly so that there were changes in the SMP Negeri 1 P.Batu school with more and more interested students because the school has quite a lot of students, even from year to year the number can be up to 400 per student. with the same goal, namely to educate the nation's children and create a better character and character of students.